Evaluation of Peri‐Implant Bone Repair of Commercially Pure Titanium or Titanium‐Aluminum‐Vanadium Alloy Implants With or Without Laser‐Modified Surface - de Jesus, Laís Kawamata [UNESP]; Hadad, Henrique [UNESP]; da Silva, Luis Fernando Alves [UNESP]; de Souza Rodrigues, Letícia Gabriella [UNESP]; Santos, Ana Flávia Piquera [UNESP]; Queiroz, Thallita Pereira; Piazza, Rodolfo Debone [UNESP]; Guastaldi, Fernando Pozzi Semeghini; Poli, Pier Paolo; Maiorana, Carlo; Guastaldi, Antonio Carlos [UNESP]; Okamoto, Roberta [UNESP]; et al. (Wiley, 2025)
To evaluate the peri-implant bone repair of implants manufactured from commercially pure titanium (cp-Ti) or titanium-aluminum-vanadium alloy (Ti-6Al-4 V) with machined (MS) or laser-modified (LS) surfaces. Implants (n = 192) were installed in the tibias of 96 rats and divided according to the implant installed: (1) cpMS: cp-Ti with an MS surface, (2) cpLS: cp-Ti with an LS surface, (3) alloyMS: Ti-6Al-4 V with an MS surface, and (4) alloyLS: Ti-6Al-4 V with an LS surface. Scanning electron microscopy-energy dispersive X-ray (SEM-EDX) analysis was performed prior to implant placement. At 14, 21, and 42 days, biomechanical analysis, SEM-EDX of the removed implants, and measurement of the percentage of bone-implant contact (%BIC) and neoformed bone area (%NBA) were performed. At 42 days, the mineral apposition rate (MAR) and bone dynamics were analyzed. At 14 and 21 days, the alloyLS group showed higher removal torque values than cpLS (p < 0.05). For SEM-EDX, the cpLS and alloyLS groups showed surfaces covered by bone tissue and higher peaks of calcium and phosphorus. No statistical differences were observed for %BIC, and at 14 days, a higher %NBA was found for alloyLS than cpLS (p < 0.05). At 42 days, in bone dynamics, alloyLS showed a higher amount of calcein compared to cpLS (p < 0.05), and higher MAR values were observed for cpLS (p < 0.05). The alloyLS group promoted accelerated peri-implant bone repair at 14 and 21 days. However, at 42 days, cpLS surpassed the values of removal torque, %BIC, %NBA, bone dynamics, and MAR.